Conservation of Natural Resource Management in the Buffer Village Community of Alas Purwo Banyuwangi National Park East Java Indonesia Based on Local Wisdom - Setiawan, Eko; Sukesi, Keppi; Hidayat, Kliwon; Yuliati, Yayuk (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2021)
This research describes the life of the people around the buffer village area of Alas Purwo National Park which has local wisdom in the form of a number of traditions, in the form of rules or restrictions that are still valid for generations. This local wisdom has the value of ecological intelligence that is maintained and developed so as not to be driven by modernization. Local wisdom owned by the community is used as a reference in the management of forest areas, both myths, abstinence. The type of research used is descriptive qualitative with sociological approach with case study design. The results showed that the community around Alas Purwo National Park area has local wisdom in the form of a number of traditions, rules or restrictions that are still valid for generations that are then maintained and obeyed until now. The restriction is in the form of a ban on killing peacocks and menco and abstinence in the payang system.Â DOI:Â https://doi.org/10.26905/lw.v13i1.5109